الثقة بالنفس وعلاقتها بالأداء المهني، وفق عدة أساليب تقييم، لدى طلاب الدبلوم العالي، في تعليم اللغة العربية لغير الناطقين بها - علي، أحمد رمضان محمد (جامعة أسيوط - كلية التربية, 2022)
تهدف الدراسة الحالية إلى التعرف على الثقة بالنفس، وعلاقتها بالأداء المهني لدى طلاب الدبلوم العالي، في تعليم اللغة العربية لغير الناطقين بها. وتكونت عينة الدراسة من (٢٣) طالبا وطالبة من طلاب وطالبات الدبلوم العالي، في تعليم اللغة العربية لغير الناطقين بها، في الفصل الدراسي الثاني، للعام الدراسي 2021-2022 م، طبق عليهم مقياس الثقة بالنفس، وبطاقة ملاحظة الأداء المهني، لطلاب الدبلوم العالي، في تعليم اللغة العربية لغير الناطقين بها. والتي تم تطبيقها من خلال أستاذ المقرر ومقيم خارجي، وتقييم ذاتي وتقييم الأقران. وأشارت نتائج الدراسة إلى أنه يوجد مستوى كبير من مستوى الثقة بالنفس، لدى عينة البحث. ويوجد مستوى كبير جدا من مستوى الأداء المهني لدى عينة البحث، وفقا لتقييم أستاذ المقرر. ولا يوجد فرق دال إحصائيا في الثقة بالنفس، لدى عينة البحث، وفقا للنوع (ذكور-إناث). ولا يوجد فرق دال إحصائيا في مستوى الأداء المهني لدى عينة البحث، وفقا للنوع (ذكور-إناث)، ووفقا لتقييم أستاذ المقرر. ولا توجد علاقة بين الثقة بالنفس والأداء المهني، لدى عينة البحث، في حالة تقييم الأداء المهني من أستاذ المقرر والمقيم الخارجي والتقييم الذاتي. ويوجد فرق دال إحصائيا، في مستوى الأداء المهني، لدى عينة البحث، وفقا لتقييم (المقيم الخارجي-تقييم الأقران)، لصالح تقييم الأقران. ولا توجد فروق دالة إحصائيا، في مستوى الأداء المهني، وأبعاده الفرعية، لدى عينة البحث، وفقا للتقييم الذاتي وتقييم الأقران. This study aims to identify self-confidence and its relationship to professional performance among high diploma students in teaching Arabic to non-native speakers. The study sample consisted of (23) male and female high diploma students, in teaching Arabic to non-native speakers, in the second semester of the academic year 2021-2022 AD; The self-confidence scale and the professional performance observation list were applied to high diploma students in teaching Arabic to non-native speakers, through the course professor and an external assessor, and self-assessment and peer assessment. The results of the study indicated that there is a large level of self-confidence in the research sample. There is a very high level of professional performance for the research sample, according to the assessment of the course professor. There is no statistically significant difference in self-confidence among the research sample, according to gender (male-female). There is no statistically significant difference in the level of professional performance of the research sample, according to gender (male-female), and according to the assessment of the course professor. There is a relationship between self-confidence and professional performance, among the sample, in the case of peer assessment of professional performance. There is no relationship between self-confidence and professional performance, among the research sample, in the case of professional performance assessment by the course professor, external assessor and self-assessment. There is a statistically significant difference in the professional performance of the research sample, according to the assessment of (external evaluator - peer assessment), in favor of peer assessment. There are no statistically significant differences in the level of professional performance and its sub-dimensions among the research sample, according to self- and peer assessment.
Keywords: الأداء الدراسي -- إعداد المعلمين -- الناطقين بغير العربية -- طلبة الدبلوم العالي